A sudden case of Christmas [videorecording (DVD)] - Chelsom, Peter, 1956-; Lindsay, Tinker; Bomprezzi, Gianluca; Parenti, Neri, 1950-; Baccomo, Federico, 1978-; Patierno, Francesco; DeVito, Danny; MacDowell, Andie; Valderrama, Wilmer, 1980-; DeVito, Lucy, 1983-; Dunbar, Adrian, 1958-; Zúñiga, José; et al. (Shout! Factory, 2024)
An American couple bring their 10-year-old daughter, Claire, to her grandfather Lawrence's hotel in The Dolomites, Italy. They usually come for Christmas but this year it's August. The fact is they are breaking up and want Lawrence to be the one to tell Claire, especially as he has such a special relationship with his granddaughter. Once Claire realizes there's not going to be a family Christmas this year, she insists on everyone making it Christmas right here, right now in August, including flying in her other grandparents. Claire, in collusion with her grandfather, plan activities that are designed to re-unite her parents. The whole process backfires and puts her grandparents' marriage into unexpected difficulties.